РЕЖИМИ РОБОТИ ПІДВИЩУЮЧОГО ПОСТІЙНУ НАПРУГУ ПЕРЕТВОРЮВАЧА ЕНЕРГЕТИЧНОГО МОДУЛЯ ВІДНОВЛЮВАНИХ ДЖЕРЕЛ ЕНЕРГІЇ - Войтех, В.О. (Інститут електродинаміки Національної академії наук України, 2023)
The processes in the step-up DC voltage converter, as an element of the power module powered by DC voltage renewable energy sources 30 to 350 V, were studied. The main modes of operation (continuous and intermittent) were considered, as well as various options for ratios between the duration of the closing intervals of the power switch of the converter, input voltage, choke and load parameters. Graphs showing the processes in the converter are given. Ref. 3, fig. 2, tables 2.